Ga@MXene-based flexible wearable biosensor for glucose monitoring in sweat - Zhang, Wensi; Jiang, Shuyue; Yu, Hongquan; Feng, Shilun; Zhang, Kaihuan (iScience, 2025)
Most wearable biosensors struggle to balance flexibility and conductivity in their sensing interfaces. In this study, we propose a wearable sensor featuring a highly stretchable, three-dimensional conductive network structure based on liquid metal. The sensor interface utilizes a patterned Ga@MXene hydrogel system, where gallium (Ga) grafted onto MXene provides enhanced electrical conductivity and malleability. MXene provides excellent conductivity and a three-dimensional layered structure. Additionally, the chitosan (CS) hydrogel, with its superior water absorption and stretchability, allows the electrode to retain sweat and closely stick to the skin. The sensor demonstrates a low limit of detection (0.77 μM), high sensitivity (1.122 μA⋅μM⁻1⋅cm⁻2), and a broad detection range (10–1,000 μM), meeting the requirements for a wide range of applications. Notably, the sensor can also induce perspiration in the wearer. The three-dimensional porous structure of the Ga@MXene/CS biosensor ensures excellent conductivity and flexibility, making it suitable for a variety of applications. [Display omitted] •The electrochemical glucose detection was performed on the Ga@MXene/CS-based wearable sensor•The sensor features a conductive, three-dimensional porous structure based on Ga@MXene•The sensor has a linear range of 10–1,000 μM, a limit of detection as low as 0.77 μM•In real sample testing, the recovery rate of the sensor ranged from 95.5% to 107.1% Health sciences; Natural sciences; Applied sciences